Impact of technological factors on diamine oxidase (DAO) activity in porcine kidney extracts as active ingredient for the dietary management of histamine intolerance - Judit Costa-Catala; Salvador Pellicer-Roca; Irache Iduriaga-Platero; Sònia Sánchez-Pérez; M. Teresa Veciana-Nogués; M. Luz Latorre-Moratalla; M. Carmen Vidal-Carou; Oriol Comas-Basté (Applied Food Research)
Histamine intolerance is associated with impaired histamine metabolism due to diamine-oxidase (DAO) enzyme deficiency at intestinal level. The recommended strategy to alleviate the symptomatology is a low-histamine diet supplemented with DAO. Different sources of DAO enzyme have been characterized in the literature (animal, vegetal and microbial), although only the porcine kidney protein extract has been approved as food supplement. Despite optimistic clinical results of DAO supplementation, variability in enzymatic activity of this type of active ingredient is reported, potentially linked to manufacturing processes. The aim of this work was to evaluate the impact of the raw material and the technological process of obtaining the porcine kidney protein extract on DAO activity, and its evolution during storage at room temperature (25 °C) and refrigeration (4 °C). Twenty batches of DAO-containing extract were analyzed and found to have a consistent histamine-degrading activity. The powder extract was prepared by mincing and homogenizing porcine kidneys, defatting with acetone, and drying at 40 °C for 6 h. The inclusion of a biocidal step before acetone extraction was evaluated on DAO activity. The use of sodium hypochlorite and irradiation (8kGy) did not have a negative impact on DAO activity. Moreover, the inclusion of an initial freeze-drying step of the raw material yielded an extract with higher DAO activity. On the other hand, the effect of applying higher temperatures (70 °C, 80 °C, and 90 °C) during the extract drying process for 3 and 6 h was evaluated, reporting a significant decrease of the enzymatic activity, with losses of 10–20 % for every 10 °C increase in temperature. Refrigeration was the only storage method capable of preserving enzymatic activity for at least 24 months. The manufacturing and storage of porcine kidney extract are crucial steps in the formulation of DAO supplements suitable for the treatment of histamine intolerance.